2017
DOI: 10.3758/s13423-017-1309-5
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting from lapses of sustained attention

Abstract: When performing any task for an extended period of time, attention fluctuates between good and bad states. These fluctuations affect performance in the moment, but may also have lasting consequences for what gets encoded into memory. Experiment 1 establishes this relationship between attentional states and memory, by showing that subsequent memory for an item was predicted by a response time index of sustained attention (average response time during the three trials prior to stimulus onset). Experiment 2 stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 33 publications
7
109
0
Order By: Relevance
“…Previous research has studied interactions between sustained attention and subsequent memory using controlled psychological tasks that measure participants' memory for stimuli encountered in different attentional states. For example, participants in a study from deBettencourt et al 4 performed a CPT and then reported their incidental recognition memory of the presented images. CPT stimuli seen during engaged attentional states (indexed with response times) were better remembered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has studied interactions between sustained attention and subsequent memory using controlled psychological tasks that measure participants' memory for stimuli encountered in different attentional states. For example, participants in a study from deBettencourt et al 4 performed a CPT and then reported their incidental recognition memory of the presented images. CPT stimuli seen during engaged attentional states (indexed with response times) were better remembered.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Such fluctuations of attention not only influence our ongoing perceptual experience, but can also have consequences for what we later remember. 4 Changes in attentional states are typically studied with continuous performance tasks (CPTs), which require participants to respond to rare targets in a constant stream of stimuli or respond to every presented stimulus except the rare target. [5][6][7] Paying attention to taxing CPTs, however, often feels different than paying attention in other everyday situations.…”
Section: Introductionmentioning
confidence: 99%
“…Since the seventies, the list-wide PC manipulation has been extensively employed to index the context-sensitive modulation of attention in tasks such as Stroop color-naming (e.g., Cheesman & Merikle, 1986;Glaser & Glaser, 1982;Kane & Engle, 2003;Lindsay & Jacoby, 1994;Logan, 1980;Logan & Zbrodoff, 1979;Lowe & Mitterer, 1982;Shor, 1975;West & Baylis, 1998). The list-wide PC manipulation varies the relative frequency of congruent (e.g., the word "blue" displayed in blue ink) to incongruent (e.g., the word "red" displayed in blue ink) trials across list contexts (e.g., mostly congruent vs. mostly incongruent lists; for reviews and a user's guide to the manipulation, see Bugg, 2012Bugg, , 2017Bugg & Crump, 2012).…”
Section: Assessing the Temporal Learning Account Of The List-wide Promentioning
confidence: 99%
“…Sustained attention fluctuates between advantageous and disadvantageous states over time. These trial-by-trial fluctuations of sustained attention predict which items are later remembered (deBettencourt et al, 2018). In fact, fluctuations of sustained attention remain a key candidate explanation for previous demonstrations of pre-trial states that predict long-term memory (Gruber & Otten, 2010;Guderian et al, 2009;Otten et al, 2006;Weidemann & Kahana, 2020).…”
Section: Introductionmentioning
confidence: 85%